HUBUNGAN ANTARA PENGGUNAAN VIDEO INTERAKTIF TERHADAP HASIL BELAJAR FISIKA SISWA SMA NEGERI 1 BATAHAN - Yualda; Sriutami Kholilla Mora Siregar; Eni Sumanti Nasution (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2026)
This study aims to determine the relationship between the learning environment and students' learning concentration. This study uses quantitative methods with correlational methods. This study was conducted at SMA Negeri 1 Batahan with a sample of 30 students. This study uses correlational analysis and simple linear regression. Sampling uses a purposive sampling method. The data instrument used is a questionnaire. According to (Sugiono, 2018) a questionnaire is a data collection technique by providing written questions to respondents to be answered. There are 2 variables in this study, namely the interactive video variable (X) and the learning outcome variable (Y). Based on the data obtained using SPSS 23 software, it was found that the significance of both variables, namely the learning environment questionnaire and the learning concentration questionnaire, was 0.07, which means it is smaller than 0.05, which means there is a relationship between the learning environment and the learning concentration of students at SMA Negeri 1 Batahan.